Densification Strategy: Sustainability Analysis of Co-Housing Typology - Mohd Rodzi, Khairul Asyraf; Mohd Hamberi, Mohd Jamil; Lang, Luciana (International Journal of Sustainable Construction Engineering and Technology, 2022)
Densification strategy through co-living typology seems to be a sustainable solution to current global issues: increasing in human population, housing crisis and inflated prices. However, the characteristic of the typology that able to house high significant number of people on a piece of land create a dispute, especially on the dwellers’ comfort. Thus, the aim of the research is to identify the performance of the typology to the inhabitants. Components such as floor plan area, daylighting and ventilation aspects are employed in the research to justify the sustainability of the typology to the inhabitants. The components were based on the space standard, Average Daylighting Factor (ADF) and sDA (Spatial Daylight Autonomy) through Sefaira analysis and simulation, and guidelines from Manchester City Council (2017) through Manchester Residential Quality Guidelines (MRQG) and Sinha (2014) respectively. The research was focusing on ongoing construction of the Echo Street Co-Living in Manchester, UK. From the analysis, the finding generally shows the typology manages to achieve a sustainable-performance unit through area and dimension, as well as ventilation aspects, even though there is a minor flaw, especially in providing an adequate level of daylighting. The result from the research could be used as a reference to design a high performance co-living unit in the future.